Physico-mechanical and water absorption properties of LDPE /cassava starch film / Junaidah Jai …[et al.] - Jai, Junaidah; Abd Karim, Siti Fatma; Md Zaki, Nurul Asyikin; Abdol Aziz, Rabiatul Adawiyah; Wahet, Farhana; Shaharuddin, Nadiah Shafiqah (Universiti Teknologi MARA, 2021)
Plastic waste is a global crisis, and Malaysia is the 8th worst country worldwide for plastic waste. With this trend, growing market demands for green product have imposed pressure on industries to find an alternative to petroleum-based plastic. Degradable plastic is introduced to overcome this limitation. The present work investigates degradable plastic film of low-density polyethylene incorporated with cassava starch (LDPE-CS). The compounding of the LDPE-CS was prepared via pre-mixing, blending, resin crushing, and film hot pressing. Film thickness, tensile strength, elongation, water absorption, and field test were conducted on the LDPE-CS and commercial LDPE (control). Experimental data of LDPE-CS and commercial LDPE films were evaluated and compared. Thickness of LDPE-CS film was 0.18 mm which was 51% thicker than the control film. Tensile strength and elongation of the LDPE-CS were 7.04 MPa and 5.39%, while control film was 12.77 MPa and 921.5%, respectively. The tensile strength and elongation of the LDPE-SC were significantly lower than the control film, which may be due to the weak interface between LDPE and starch. The water absorption test revealed that the LDPE-CS film absorbed water by 4.8%, which indicates its degradability in the water. The field test shows that the LDPE-CS is biodegradable and comparable with the commercial plant polybag in terms of its capability in planting.